Challenges Faced by Libyan Dental Practitioners in Endodontic Treatment - Amal Kashelaf; Sumaya Aghila; Nizar Belhaj (Khalij-Libya Journal of Dental and Medical Research, 2024)
Objectives. The purpose of this study was to recognize the most challenging aspects of root canal treatment encountered by Libyan dental practitioners. Methods: A questionnaire was distributed randomly to 130 general dental practitioners who were working in Libya’s public and private dental centers and dental faculty. The data was gathered and statically analyzed. Results: The results showed that 33.8% of the respondents had some difficulties taking periapical radiographs, 45.4% experienced problems in providing proper isolation with the rubber dam, and only 32.3% reported that they faced difficulties when determining working length. The majority of respondents 74.6% had appropriate knowledge about the various irrigation procedures and 26.9% of those experiencing problems associated with difficulties shaping the canal(s).In addition, 30% of respondents were having difficulties obturating the canal; 56.4% during master cone fitting; 30.8% choosing the proper technique; and 12.8% sealer placement.76.9% of respondents had challenge mishaps cases, the most challenging mishap case they had treated was separated instrument(s) by32.3% respondents, 19.2% respondents by ledge bypass, 15.4% of them by negotiating missed canal(s) and 10.0% of them by perforation management. Conclusion. The evaluation of the challenges that dental practitioners face during root canal therapy can help in the creation of instructional plans for preclinical and clinical training. Further studies should be required about this subject, this present survey helped to ascertain various gaps in the education schedule which, if altered correctly, would be of great benefit to both the quality of dental practitioners’ performance. الأهداف. كان الغرض من هذه الدراسة التعرف على أكثر جوانب علاج قناة الجذر تحديًا التي واجهها أطباء الأسنان الليبيون. الطرق: تم توزيع استبيان عشوائيًا على 130 طبيب أسنان عام يعملون في مراكز طب الأسنان العامة والخاصة في ليبيا وكلية طب الأسنان. تم جمع البيانات وتحليلها إحصائيًا. النتائج: أظهرت النتائج أن 33.8٪ من المستجيبين واجهوا بعض الصعوبات في أخذ الأشعة السينية حول الذروة، وواجه 45.4٪ مشاكل في توفير العزل المناسب مع السد المطاطي، وأفاد 32.3٪ فقط أنهم واجهوا صعوبات عند تحديد طول العمل. كان لدى غالبية المستجيبين 74.6٪ معرفة مناسبة بإجراءات الري المختلفة و26.9٪ من هؤلاء الذين واجهوا مشاكل مرتبطة بصعوبات تشكيل القناة (القنوات). بالإضافة إلى ذلك، واجه 30٪ من المستجيبين صعوبات في سد القناة؛ و56.4٪ أثناء تركيب المخروط الرئيسي؛ و30.8٪ في اختيار التقنية المناسبة؛ و12.8% وضع مانع التسرب. 76.9% من المستجيبين لديهم حالات حوادث صعبة، وكانت حالة الحادث الأكثر تحديًا التي عالجوها هي أداة (أدوات) منفصلة من قبل 32.3% من المستجيبين، و19.2% من المستجيبين عن طريق تجاوز الحافة، و15.4% منهم عن طريق التفاوض على القناة (القنوات) المفقودة و10.0% منهم عن طريق إدارة الثقب. الاستنتاج. يمكن أن يساعد تقييم التحديات التي يواجهها أطباء الأسنان أثناء علاج قناة الجذر في إنشاء خطط تعليمية للتدريب السريري وما قبل السريري. يجب إجراء المزيد من الدراسات حول هذا الموضوع، وقد ساعد هذا الاستطلاع الحالي في تحديد الفجوات المختلفة في جدول التعليم والتي، إذا تم تعديلها بشكل صحيح، ستكون ذات فائدة كبيرة لكل من جودة أداء أطباء الأسنان